Dose–response relationship between oxytocin exposure during labor induction and neonatal hyperbilirubinemia - Liang, Yanlan; Liang, Zhidong; Zhong, Jianxin; Yue, Rong; Jiang, Xiaocui (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to investigate the association between maternal oxytocin dosage and the risk of neonatal hyperbilirubinemia.MethodsA total of 500 mothers and their neonates were retrospectively included. Based on the cumulative oxytocin dose, participants were divided into a low-dose group (n = 168), a moderate-dose group (n = 167), and a high-dose group (n = 165). Baseline characteristics and perinatal outcomes of mothers and neonates were compared across groups. Multivariable logistic regression analysis was performed to evaluate the effect of oxytocin dosage on the risk of neonatal hyperbilirubinemia. Sensitivity analysis was conducted by excluding neonates with abnormal gestational age.ResultsThe overall incidence of neonatal hyperbilirubinemia was 10% (50/500), with rates of 2.98%, 8.98%, and 18.18% in the low-, moderate-, and high-dose oxytocin groups, respectively. High-dose oxytocin significantly increased the risk of neonatal hyperbilirubinemia (odds ratio [OR] 7.933, 95% confidence interval [CI] 2.923–21.527, p < 0.001), while the moderate-dose group also showed an elevated risk (OR 3.034, 95% CI 1.059–8.692, p = 0.039). Maternal body mass index (BMI) was negatively associated with the risk (OR 0.847, p = 0.003). The dose–response curve demonstrated a clear positive correlation between high-dose oxytocin exposure and neonatal hyperbilirubinemia risk (p < 0.05). Sensitivity analysis excluding neonates with abnormal gestational age yielded results consistent with the full-sample analysis.ConclusionIncreased oxytocin dosage during labor induction is significantly associated with a higher risk of neonatal hyperbilirubinemia. Clinicians should be alert to the potential risk of bilirubin elevation in neonates exposed to high-dose oxytocin.